Arah Baru dalam Memahami Zakat: Studi Tafsir Ayat-ayat Zakat - Darul Aman (Jurnal Akademika Kajian Ilmu-Ilmu Sosial, Humaniora Dan Agama, 2022)
Religious obligatory is one of Islam foundation five. Thereby, domicile his of vital importance in the relation with keislaman someone. Besides also obligation of religious obligatory is always stringed up with obligation salat.